Documents of personal origin at the National Archives of the Republic of Tuva - Chamzo, Dolaana U. (The New Research of Tuva, 2020)
The article examines the history of collections containing documents of personal origin at the National Archives (prior to 07.04.2020 known as the State Archives) of the Republic of Tuva. The article presents an overview of these collections and a more in-depth analysis of some of them. All in all, there are 63 personal collections at the archives, totaling 4556 archival units.The first sets of documents of personal origin were acquired in mid-1950s, when they started collecting memoirs and memorabilia of those who participated in the revolutionary events of 1917-1921 in Uriankhai Territory, as Tuva was known in early 20th century. Since 1958, work has been getting more and more meaningful and dedicated. The Archive’s fonds have been expanded a number of times, and the public interest in archival storage of documents has been increasing in 1980s and 1990s. Between 2014 and 2018, 18 personal collections were added to the Archives, altogether containing about 800 archival units. Most of these are documents related to politicians, notable figures in Tuvan culture and fine arts, veterans and Tuvan volunteers in the Great Patriotic War (WWII). A special place in the archives belongs to the S.K. Toka collection. S.K. Toka was a renowned political figure and Communist Party functionary in Soviet Tuva. This collection has been classified as ‘highly valued’.Two collections of the documents which belonged to Maksim Monguzhukovich and Kara-Kys Namzatovna Munzuk, a creative couple, have been joined to form a “family archive”. The article presents an overview of the documents in the new collection, totaling 254 archival units. A collection of documents belonging to the famous singer, Nikolai Oskeyevich Olzei-ool, is quite interesting and sadly, remains understudied. The archive also preserves the Mongush Borakhovich Kenin-Lopsan collection. Kenin-Lopsan, a renowned historian, donated some documents to the Archives himself.The total share of personal collections in the National Archives is quite small. In order to expand it and vary the sources of acquisition, an action plan has been developed. It aims to develop a methodology of engaging prominent people of the region who played a crucial role in its development.
Keywords: Tuva; personal collection; archives; archival work; Salchak Kalbakhorekovich Toka; Maksim Monguzhukovich Munzuk; Nikolai Oskeyevich Olzei-ool; Mongush Barakhovich Kenin-Lopsan; Tuvan culture; history of Tuva; State Archives of the Republic of Tuva; Nation